Identifying the factors associated with depressive symptoms among postpartum mothers in Kathmandu, Nepal - Babu Ram Bhusal; Nisha Bhandari (Elsevier, 2018)
Purpose: This study aimed to identify the factors associated with depressive symptoms among postpartum mothers in Kathmandu, Nepal. Method: A hospital-based cross-sectional study that included 346 postpartum mothers at 4-14 weeks after delivery was carried out. Validated Nepalese version of Edinburgh Postnatal Depression Scale with cut-off value of ≥12 was used to screen depressive symptoms and structured questionnaires were used to identify the associated factors. Possible factors associated with depressive symptoms were identified by logistic regression analysis. Result: The mean age of the mothers was 22.75 (SD = 4.51). The prevalence of depressive symptoms among postpartum mothers was 17.1% (95% CI = 15.07-19.12). No significant association existed between postpartum depressive symptoms and socio demographic and economic characteristics. In multivariate analysis, risk factors for postpartum depressive symptoms were identified as follows: women without adequate rest during pregnancy (aOR = 4.023, 95% CI = 1.294-12.501), abortion history (aOR = 3.25, 95% CI = 1.208-9.065), poor relationship with husband (aOR = 1.67, 95% CI = 1.073-8.384), marital dissatisfaction (aOR = 4.053, 95% CI = 2.281-12.819) and stressful life events (aOR = 3.89, 95% CI = 1.504-9.810). Conclusions: This study aids to draw attention on the incorporation of routine screening for basic support and intervention for identified risk factors in postpartum period. Policies can be formulated to encourage postpartum women to obtain adequate rest during pregnancy, support women with poor partner relationship, reduce marital dissatisfaction, help women adjust with stressful life events, and prevent and manage abortion appropriately. These policies may reduce harmful consequences of postpartum depressive symptoms for women, newborn and their family. Keywords: Edinburgh postnatal depression scale (EPDS), Nepal, Postpartum depressive symptoms